2017
DOI: 10.3233/jad-161225
|View full text |Cite
|
Sign up to set email alerts
|

Trends, Predictors, and Outcomes of Healthcare Resources Used in Patients Hospitalized with Alzheimer’s Disease with at Least One Procedure: The Nationwide Inpatient Sample

Abstract: We assessed trends, predictors and outcomes of resource utilization in hospital inpatient discharges with a principal diagnosis of Alzheimer's disease (AD) with at least one procedure. Using Nationwide Inpatient Sample data (NIS, 2002–2012), discharges primarily diagnosed with AD, aged ≥60 y and with ≥1 procedure, were selected (Weighted N= 92,300). Hospital resource utilization were assessed using ICD-9-CM codes, while hospitalization outcomes included total charges (TC, 2012$), length of stay (LOS, days), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 31 publications
0
13
0
3
Order By: Relevance
“…Our findings are contrary to most previous reports about LOS in dementia patients. Studies have reported a longer LOS for patients with dementia in the past [ 12 , 13 , 21 ], which is usually attributed to associated health complications leading to worse health status, including impaired orientation, functional abilities, and risk of fall [ 13 , 15 ]. Unlike our study, past studies have used data from patients with multiple comorbidities admitted to hospital for acute illnesses not related to hip fracture or OP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our findings are contrary to most previous reports about LOS in dementia patients. Studies have reported a longer LOS for patients with dementia in the past [ 12 , 13 , 21 ], which is usually attributed to associated health complications leading to worse health status, including impaired orientation, functional abilities, and risk of fall [ 13 , 15 ]. Unlike our study, past studies have used data from patients with multiple comorbidities admitted to hospital for acute illnesses not related to hip fracture or OP.…”
Section: Discussionmentioning
confidence: 99%
“…However, women and Whites were more likely to have lower hospital charges that men and non-Whites. One study attributed higher hospital charges for inpatients with dementia due to their comorbidities complicating acute illness and a need for additional in-hospital procedures compared to the hospitalized non-dementia counterparts [ 12 ]. Having CHF or IHD posed risk to those having higher charges in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study has several limitations. First, consistent with prior studies, we relied on hospital diagnosis coding to identify patients diagnosed with dementia; this approach underestimates the prevalence of dementia and does not provide information on severity of dementia 20,21 . Although we used diagnosis codes specific to dementia, they are not sensitive for mild cognitive impairment that frequently goes undiagnosed in outpatient settings 48 and may be misdiagnosed as delirium during hospitalization.…”
Section: Discussionmentioning
confidence: 99%